Optimizing English Language Learning Competence Based Religious Moderation at the State Islamic Higher Education - Mujahidah; Anwar; Dj, Muhammad Zuhri; Shafa; Sulastri (Association of Language Teachers in Southeast Asia (ALTSA), 2025)
The English language plays a pivotal role in education, particularly in global contexts. It is utilised in various domains, including education, business, and diplomacy. Moreover, it can be integrated with Islamic studies, particularly Islamic moderation, which emphasises balance, tolerance, and peaceful coexistence. This study addresses a research gap by investigating the impact of religious moderation on students' learning competence in speaking classes, a topic that has received limited attention in previous studies. This research aims to investigate students’ learning competence in religious moderation at the English Department of the Tarbiyah Faculty of IAIN Parepare. This research was conducted from March to June 2024. This mixed-method study combines qualitative and quantitative data to provide a comprehensive understanding. Twenty students from the fifth semester participated, and data were collected through interviews and documentation. The findings indicate that religious moderation is effectively implemented in speaking classes through three stages: preparation (lecture planning with RPS), implementation (using materials from YouTube, podcasts, articles, and videos), and evaluation (role-playing videos to assess competence). The students' scores increased from 77.0 to 85.76, showing significant improvement. The study shows that integrating religious moderation in speaking classes enhances language competence, with positive students’ perceptions confirming it as an effective teaching strategy.